Effectiveness of Hae-Band in Measuring Hb Levels in Postpartum Hemorrhage Risk Monitoring - Meidita, Dinda Dian; Wijayanti, Krisdiana; Hendriyani, Heni (JURNAL INFO KESEHATAN, 2024)
Postpartum hemorrhage is the main cause of high morbidity in the world (75%). Until now, efforts to early detect the risk of postpartum hemorrhage have still not been maximized. Sensor-based smartband can be the development of non-invasive methods in an effort to early detection of declining Hb levels in monitoring the risk of bleeding with practical, fast, precise, accurate, and practical. This research aims to determine the effectiveness of developing and analyzing the effectiveness of the "Hae-band" smartband in monitoring the risk of postpartum hemorrhage. The research method used is Research and Development (R&D), a quasi-experimental one-group pretest-posttest design using a nonequivalent dependent variable. The sampling technique in this research uses non-probability sampling with purposive sampling type. Respondents were selected by purposive sampling with a sample of 35 respondents maternity up to 6 hours postpartum to measure Hb levels and analyze the average levels of Hb and declining levels of HB Hae-band, HB meter POCT and visual estimation of blood loss volume compared with HB meter POCT (gold standard). Data analysis using the descriptive test, validation test, Paired T-Test, Independent T-Test, and multiple linear regression. The research results show that the Hae-band has been developed and is feasible as a measure of Hb levels which has a sensitivity of truth tool as much as 70.0% and can detect a decrease in Hb levels as much as 63.9% (p=0.000) more partially effective than visual estimation (0.24%) Smartband can detect Hb levels with good results compared to the gold standard of blood tests with a difference of 0.324 g/dL (p.0.113) with an average Hb levels at 6 hours PP at 11.19 g/dL compared to the average POCT 11.34 g/dL. This research concludes that Hae-band is more effective in detecting postpartum hemorrhage risk than visual estimation. It is hoped that further research can develop a more modern design where the sensor is more comfortable to use for long periods and has an alternative way of reading the sensor other than on the wrist. Improving accuracy, sensitivity, and higher battery power by improving the type of design, sensor, and wave type to be more suitable for measuring Hb levels can also be developed considering the efficiency of maternal monitoring and recording in the era of digitalization in early detection of bleeding risk.